2022
DOI: 10.1093/qjmed/hcac060
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 HSV encephalitis: a review

Abstract: Background Herpes simplex virus encephalitis (HSVE) is one of the most common infectious cause of sporadic encephalitis. COVID-19 has been associated with immune dysregulation of the host which might increase the risk of infections like HSVE following SARS-CoV-2 infection. There is paucity of literature on post COVID-19 HSVE. This study was conducted with the aim of analysing the clinical presentation, brain imaging, and outcome of patients presenting with HSVE within six weeks of COVID-19 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Another observational study described 8 patients with laboratoryconfirmed herpes simplex encephalitis who had a history of COVID-19 within the previous 6 weeks and followed them for 3 months. In this report, all the patients received 14-day course of acyclovir and all but one with rhinocerebral mucormycosis survived Gupta et al (2022).…”
Section: Discussionmentioning
confidence: 73%
“…Another observational study described 8 patients with laboratoryconfirmed herpes simplex encephalitis who had a history of COVID-19 within the previous 6 weeks and followed them for 3 months. In this report, all the patients received 14-day course of acyclovir and all but one with rhinocerebral mucormycosis survived Gupta et al (2022).…”
Section: Discussionmentioning
confidence: 73%
“…Carneiro et al [45] reported a 40% incidence of neurological symptoms among patients with HSV reactivation. Four case reports of encephalitis [48][49][50][51] and one case of cerebellitis [47] have been found in the current literature review. The image patterns, sites of injury, signs and symptoms in neurological disorders seen in severe SARS-CoV-2 infection are highly heterogeneous [83], but HSV encephalitis presents well-known features, including an acute, necrotizing form that is almost always focal and often asymmetrical, located in the orbitofrontal and temporal lobes, with involvement of the cingulate and insular cortex [84][85][86].…”
Section: Detection Methods Clinical Presentationmentioning
confidence: 99%
“…(11) In fact, a recent study observed the occurrence of HSV encephalitis in post-coronavirus disease (COVID) syndrome patients, possibly caused by reactivation during immune dysregulation in SARS-CoV-2 infection. (12) Several studies have proposed an association between HSV-1 infection and neurodegenerative disease. (8,13) It is hypothesised that HSV-1 modulates neuronal 1920 (1) 1952 (17) 1964 (71) 1956 (26) 1986 (40) 1988 (41) 1990 (60) 1994 (80) Name Herpes simplex virus 1 Human betaherpesvirus 7…”
Section: Alphaherpesvirusmentioning
confidence: 99%
“…11 ) In fact, a recent study observed the occurrence of HSV encephalitis in post-coronavirus disease (COVID) syndrome patients, possibly caused by reactivation during immune dysregulation in SARS-CoV-2 infection. 12 …”
mentioning
confidence: 99%